1990
DOI: 10.2172/10114451
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the controlled release of radionuclides from waste packages containing borosilicate waste glass

Abstract: PNL-7591 UC-802 previously reached a similar conclusion (NAS 1983), as have other national repository programs (K8S 1983; NAGRA 1985). Data from the WAPS test is largely irrelevant, therefore, to the release-rate performance at either the waste-packages or EBS level of analysis. Radionuclide solubility limits are key to establishing predictive reliability and safety for geologic disposal; obtaining such data should be one priority for future tests that are intended to support the performance assessment of defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In the repository the main release scenario will occur because of reaction between liquid water and pre-aged glass. Preliminary performance assessment studies [5] that compare the release of radionuclides for glass and spent fuel have concluded that glass can provide a significant proportion of the radionuclide release for the overall repository. To refine this assessment and to provide a bounding limit to radionuclide release, further testing of pre-aged glass must be performed.…”
Section: E Ongoingworkmentioning
confidence: 99%
“…In the repository the main release scenario will occur because of reaction between liquid water and pre-aged glass. Preliminary performance assessment studies [5] that compare the release of radionuclides for glass and spent fuel have concluded that glass can provide a significant proportion of the radionuclide release for the overall repository. To refine this assessment and to provide a bounding limit to radionuclide release, further testing of pre-aged glass must be performed.…”
Section: E Ongoingworkmentioning
confidence: 99%
“…Related to this topic is the known tendency for some glasses to precipitate specific secondary phases in leach tests. For example, high alumina glasses will alter to form analcime and maintain lower levels of dissolved silica than glasses with lower alumina contents [119]. The lowered dissolved silica concentrations 44 will increase glass dissolution rates.…”
Section: Issues Needing Investigationmentioning
confidence: 99%
“…These tests should cover a wide range of surface area-to-volume ratios (SA/V). By using the pH stat technique, high SA/V tests should scale with low SAN tests when normalized using SA/V-t. High SA/V tests in closedsystem tests with free-drift pH do not scale because of early rapid ion exchange that causes high SA/V solutions to react at higher pH values than low SA/V solutions [119]. Using high SA/V as an accelerated test procedure is justified if all system parameteters are measured and the reaction mechanism does not change.…”
Section: Types Of Experiments Neededmentioning
confidence: 99%
“…The ion-exchange process has been largely ignored because it has been thought to be a short duration, secondary, or tertiary process that had little or no bearing on long-term corrosion or radionuclide release rates from glasses. The only significant effect identified in the literature that is attributed to alkali ion exchange is an increase in solution pH in static laboratory tests conducted at high surface area-to-volume ratios (Strachan et al 1990;Bourcier and Feng 1993).…”
Section: Effect Of Ion Exchangementioning
confidence: 99%